Application of the Mechanical and Pressure Drop Tests to Determine the Sintering Temperature of Coal and Biomass Ash - Karol Król; Dorota Nowak-Woźny (Energies, 2021)
The aim of this paper is to investigate the mechanical properties of coal and biomass ash during the sintering process. For this study, bituminous coal, lignite, wheat straw, barley straw, and rye straw were selected. The proximate, ultimate, and oxide analyses were performed. The ash from these fuels was prepared in a special way that ensured the physicochemical invariability of the initial state of the mineral matter of coal and biomass. The purpose of this selection was to obtain widely available and clearly diversified materials. Based on the results of ash composition and ultimate analysis the most common ash deposition, indices were determined. Certain conflict of index indications was observed. Then, the mechanical test and pressure drop test were performed. During the mechanical test, the fracture stress as a function of sintering temperature was measured. During the pressure drop test, the pressure before and behind the sample was measured as a function of sintering temperature. Both tests showed that the characteristic changes (the occurrence of a maximum on the pressure drop curve and the inflection point at the mechanical curve) dependencies were at nearly the same temperatures. These results were compared with the initial deformation temperature (IDT) from the standard Leitz method. A linear relationship between sintering temperatures determined by the mechanical test, pressure drop test, and IDT Leitz test was obtained. The obtained results are promising in terms of the application of the mechanical methods (fracture stress test and pressure drop test) as methods of the early stage prediction of slagging/fouling risks.